Competitiveness Management Based on Factors of Customer Perception of Goods and Services - A. A. Meshkov (Plekhanov Russian University of Economics, 2020)
The authors of the article showed the necessity in today’s conditions to include esthetic (sensual) component in communications with customers. The current standing of the subject in academic literature is depicted, practical use of scientists’ theoretical achievements is shown and concrete examples from world practice are investigated. To use effectively customer emotions and perception in marketing management in general and in shaping goods and services offer it is needed together with marketing research, which is usually done in order to find out the attitude of potential customers to basic customer characteristics being offered to test product or service on expected emotional perception. As a result of the subject analysis the authors pointed out to objective preconditions for further and deeper research in this direction. Topicality of this problem researching follows from the necessity to strengthen the emotional element in marketing. Adding the emotional component to customer value can provide a serious advantage for promoting new goods and services and renewing the image of existing ones and brands as a whole.